University Students Who Overcame Learned Helplessness: What Helped or Hindered? - Hayes, Syler; Doucet, Daniele; Bedi, Robinder P. (Canadian Journal of Counselling and Psychotherapy, 2021)
Learned helplessness in an academic environment often affects educational performance and mental health in adverse ways (Ciarrochi et al., 2007; Hu et al., 2015). Using a modified version of the Enhanced Critical Incident Technique, this study aimed to develop a better understanding of what helps or hinders university students in overcoming learned helplessness. Analysis generated 14 categories of helping incidents and seven categories of hindering incidents, most of which were consistent with previous research. This study identified the category Being in the Spotlight, which had not been noted at all in past research. Examination of the results contributes information about reported interactions between hindering incidents and the importance of autonomy in overcoming learned helplessness, topics neglected or understudied in past research on learned helplessness in university students. Overall, the results of this study provide additional direction for counsellors working with university students who experience learned helplessness and highlight the need for further research to understand in more detail the helping and hindering factors outlined in this study.